Review of Fuzzy Multi-Criteria Decision Making Methods for Intelligent Supplier Selection - AKBURAK, DİLEK (Springer International Publishing, 2022)
Supplier selection is a focal process that affects the quality and cost performance of the company. Therefore, it is one of the well-known decision making problems that researchers and practitioners are most interested in. In order to choose the most strategic supplier, determining and prioritizing the selection criteria and choosing the appropriate method(s) directly affect the supply chain performance. In this study, the publications focused on multi-criteria decision making (MCDM) on the supplier selection problems in the uncertain environment are reviewed from 2017 to the present (Feb. 2022). Due to the effect of uncertainty and vagueness, most recent approaches developed for supplier selection, are constructed by integrating MCDM approach(es) with fuzzy set theory. The most widely applied and integrated fuzzy MCDM methods are stated as AHP, ANP, TOPSIS, and VIKOR. These studies are categorized into single or multiple/integrated MCDM approach(es) with different fuzzy sets in various application industries. This study contributes to the literature to examine the most frequently applied and recently developed fuzzy MCDM approaches for intelligent supplier selection by considering various assessment criteria under imprecise environments. Also, newly improved ideas can be proposed with the help of the analysis of studies about intelligent supplier selection up to the present.
Intelligent and Fuzzy Systems: Digital Acceleration and the New Normal, Infus 2022
▪ Book Series: Lecture Notes in Networks and Systems.
Keywords: Fuzzy Multi-criteria Decision Making; Supplier Selection